STUDI TENTANG BATIK KERINCI DI KOTA SUNGAI PENUH - Hardanti, Elvi; Adriani, Adriani; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
Â Â¹ Prodi Pendidikan Kesejahteraan Keluarga untuk wisuda periode 100 Juni 2014 Â² Dosen Jurusan Kesejahteraan Keluarga FT-UNP This research is a descriptive qualitative approach, which aims to describe the batik Kerinci in City Sungai Penuh, include: materials and tools used, motifs and batik techniques. Results of the study revealed: Fabrics used are cotton cloth with brand mori primisima and primed, shantung, silk and semi-silk. Wax used is carik, tembok, biron and recycled wax. The dye used is composed of: 1). Natural dyes that guava leaf extract, skin jengkol, mango leaves, the contents of saffron, onion skins and indigo grass. 2). Synthetic dyestuffs is napthol, indigosol, rapite, procion and Ramazol. Tool is a pencil, centimeters, scissors, wax paper, canting klowong, canting cap, pans, stove oil, canting walls, brush, cardboard, ender, cap table, cloth gloves, rags, cotton bud, scales, aqua glass, spoon plastic, metal spoon, bowl, bucket, scoop, plastic gloves, pot, super, sedok wood, buckets and wood stove. Motifs used is: terung pirus motif, biloik (lumbung padi), Masjid Angung and ukiran Masjid Agung, kulit manis, bungo pandan, pakau imbo, tumpal, tulisan incung, lapek terawang, enceng gondok, selampit simpei, pinggiran, jangki terawang, empat jenis, sirih tanyo, bunga reflesia, cerano, keluk paku, roda pedati, bakul, daun sirih, ketupat and patah tumbuh hilang berganti. Making process include: measuring and cutting cloth (mori), mordanting, patterns, ngelowong and mencap, mencolet, nembok, coloring dan melorot. Kata kunci: Batik Kerinci, Kota Sungai Penuh